KEPUTUSAN RUMAH TANGGA DALAM MENERAPKAN PERTANIAN PERKOTAAN (Household Decisions in Implementing Urban Farming) - RASIDIN KARO KARO SITEPU; VERALIANTA BR SEBAYANG (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2023)
This study aims to determine the factors that influence household decisions in implementing urban agriculture. The research location is in Margajaya Village, Bogor City with a total of 94 households as respondents. Data analysis uses descriptive statistics and structural equation model to measure the structure of the model that describes the relationship between latent variables and their indicators. Descriptively, it is known that the community has understood the concept of urban as much as 87.23%. The most widely applied agricultural method is the tabulampot system (51.22%). Household preferences and household knowledge of urban have a positive effect on household decisions in implementing urban agriculture. Household preferences are influenced by economic, environmental and social aspects. The hypothesis which states that household preferences and knowledge of urban agriculture has a positive effect on household decisions in implementing urban agriculture is acceptable. Due to the limited agricultural land in urban areas, increasing food availability through urban agriculture is an alternative strategy, so that training and socialization of urban agriculture need to be carried out by local governments to increase public interest in implementing urban agriculture. Urban agriculture will be able to provide food for households and also become an alternative source of increasing household income.